Narrativity and violence: conceptual, ethical and methodological challenges - Reisinger, Doris; Mandry, Christof; Andresen, Sabine (Culture & theory, 2024)
Survivors' narratives are an invaluable source for the study of violence across academic fields. At the same time, they present several difficulties for academic research. Sources may be marked by the effects of trauma, the lasting impact of perpetrators' political power or blurred lines between reality and fiction. Ethical and legal problems, distances in time between a violent event and the moment of its narration, and the variation in linguistic phrasing chosen by survivors present additional problems. Based on several case studies, the contributors explore typical problems in the study of violence through survivors' narratives, and possible ways of dealing with them.